Abrasion injuries on artificial turf: A systematic review - Twomey, D. M.; Petrass, L. A.; Fleming, P.; Lenehan, K. (Journal of Science and Medicine in Sport, 2019)
Objectives: To review the incidence of abrasion injuries sustained on artificial turf playing fields and the level of evidence existing on player perceptions of abrasion injuries on these surfaces. Design: Systematic review. Method: A systematic search was performed using SPORTDiscus, Medline, Web of Science, Scopus and Science Direct databases. Inclusion criteria included: abrasion type injuries measured; conducted on artificial/synthetic turf; type of sport reported; peer-reviewed original research; English language search terms, but no language restrictions. A quality assessment was conducted using the Newcastle-Ottawa quality scale. Results: The search yielded 76 potential articles, with 25 meeting all inclusion criteria. Twenty articles were injury-based and five were perception-based. The differences in injury definition and the lack of details of the playing surfaces produced varying results on the rate of injuries on artificial turf. Regardless of the condition of the surface, the level of play, or the sport, players perceived the fear of abrasion injuries as a major disadvantage of artificial turf surfaces. Conclusions: The review highlighted the current disparity that exists between players` perceptions of abrasion injuries and the level of evidence of abrasion injury risk on artificial turf playing surfaces. There is a need for the inclusion of greater detail of playing surfaces` specifications and condition, and an injury definition sufficiently sensitive to better measure abrasion injury incidence and severity. Without this more detailed information, it is likely that the strongly perceived risk of abrasion injuries will continue as a barrier to the adoption of artificial playing surfaces.